Discursive Contestations Beyond Parliament Shaping Indonesia’s Sexual Violence Criminal Bill: Dynamics, Actors, and Legitimacy - Fajar, Habib Ferian; Semadaria, Kharisma Ratuprima; Wicaksono, Rifki Alfian; Meryadinata, Geofani Lingga; Latuconsina, Naimah; Akbar, M. Fabian (Universitas Muhammadiyah Yogyakarta, 2026)
Law Number 12 of 2022 on Sexual Violence Crimes (TPKS Law) emerged as a response to the increasing number of sexual violence cases and the inadequacy of previous legal frameworks in providing justice and protection for victims. The enactment of this law signifies the urgency of ensuring legal certainty grounded in justice, public benefit, and respect for human rights. This study examines the debate and the state’s response during the legislative process, reflecting the tension between human rights and religious morality paradigms. It highlights three main aspects: the role and interaction of various actors in shaping the debate, the construction of morality and human rights within the socio-political framework, and the juridical-political significance of the TPKS Law in forming responsive legal norms. Using a normative legal approach and theoretical analysis, the findings show that the law represents a convergence between human rights and religious morality, producing a compromise between legal and political interests. This dynamic marks a transition from repressive to responsive lawmaking, emphasizing civil society participation and legislative commitment. Ultimately, the TPKS Law stands as both a legal achievement and a product of political contestation that strengthens victim protection and upholds human dignity.